Evaluation of radiation absorption characteristics in different parts of some medicinal aromatic plants in the low energy region - Akman, Ferdi; Geçibesler, Ibrahim Halil; Kumar, Ashok; Sayyed, M. I.; Mohd Zaid, Mohd Hafiz (Elsevier, 2019)
The mass attenuation coefficients, effective atomic numbers and electron densities of different parts (aerial parts, root and flower) of four medicinal aromatic plants (Pimpinella tragium subsp. lithophila, Scutellaria orientalis subsp. orientalis, Tanacetum abrotanifolium and Stachys byzantina c. koch) have been determined experimentally using transmission beam method for gamma energies of 13.92, 17.75, 20.78, 26.34 and 59.54 keV. The obtained mass attenuation coefficients, effective atomic numbers and electron densities were validated using WinXCOM program and good agreements were obtained for all samples. The aerial parts of the Scutellaria orientalis subsp. orientalis was found to having the maximum mass attenuation coefficients and effective atomic numbers values among the present samples. The root part of the Scutellariaorientalis subsp. orientalis has bigger values of effective electron density within the selected samples The effective atomic numbers for the present samples lie in the 3.117–6.932 range and the effective electron densities lie in the range of (0.272–1.672)x1025 electrons/g.